Fanaticism and Its Impact on Mental Health: A Literature Synthesis Study in the Indonesian Context - Dian Fitria; Dhea Natashia; Jehan Puspasari (PT Nuansa Fajar Cemerlang, 2024)
The enthusiastic engagement of Indonesian society in democratic processes, particularly during presidential elections and representation selections, highlights a notable manifestation of fanaticism across various domains. This phenomenon, while not novel, often generates conflicts, tensions, and mental health challenges. Methods: This article provides an overview of the impact of fanaticism on mental health using a literature synthesis approach. A systematic search was conducted across three reputable databases: Google Scholar, PubMed, and Taylor and Francis Online. The search strategy included keywords such as